The Face of the Banjarbaru City Wetlands in Last Four Decades - Syam'ani Syam'ani; Abdi Fithria; Eva Prihatiningtyas (Center for Journal Management and Publication, 2018)
The change of Banjarbaru city status into the central government of South Kalimantan Province, has the potential to increase the need for land. This directly affects wetlands conversion activities into other forms of land closure. This research aims to map the spatial distribution of wetlands, and the spatial distribution of wetlands conversion existing in Banjarbaru City in every decade over the last four decades, ie from the 1970s to the present. Wetlands spatial data are extracted from multitemporal satellite imagery, Landsat 5 in 1973, Landsat 5 in 1989, Landsat 5 in 1997, Landsat 5 in 2007, and Landsat 8 in 2016. The method used to extract wetlands is Object Based Image Analysis (OBIA), with Full Lambda-Schedule algorithm. The research results show that over the past last decades, the total area of Banjarbaru City's wetlands has been reduced continuously. The average total reduction rate is 534.53 hectares per decade or about 53.5 hectares per year, with a linear pattern over the past four decades.